Regulatory and Juridical Reflections on the Employment and Additional Benefits of 'Employment Status' for Disabled Veterans - Morteza Motaharifard (دانش حقوق عمومی)
In the specific supportive laws for veterans since 1993, the issue of dual employment and receiving dual salaries in the commonly referred to status of 'employment and total disability' has always been a subject of discussion and dispute in legislative processes, judicial avenues, and administrative channels. Studying this supportive legislative trend raises ambiguous and contradictory points regarding the philosophy of support, the dignity and respect of veterans, their material and spiritual growth, the principle of justice, and equal opportunities for all members of society (in terms of dual employment, the right to choose a job freely, prohibition of unjust discrimination, receiving two salaries from one fund and two funds, etc.These issues, all stemming from the Constitution, the general policies of the system, and religious sources, must serve as a basis for evaluating the legislative process supporting veterans on this matter. A comprehensive review of all approved, annulled, and repealed laws, decrees, related circulars, and their alignment with higher documents and the rulings of the Guardian Council, and if necessary, judicial practices, reveals conflicting points between the high legislative goals and the enacted laws in this area. The legislative approaches show internal contradictions and lack a satisfactory alignment with wisdom in legislation. Ultimately, the justification for dual employment in the 'employment status' is unfounded, but the duality of salary can be defensible under certain conditions.The research method is descriptive-analytical, utilizing library resources.